Efficacy of Levofloxacin Based Triple and High-Dose PPI-Amoxicillin Dual Eradication Therapy for Helicobacter pylori after Failures of First- and Second-Line Therapies. (16th December 2014) - Okimoto, Kenichiro; Arai, Makoto; Saito, Keiko; Minemura, Shoko; Maruoka, Daisuke; Matsumura, Tomoaki; Nakagawa, Tomoo; Katsuno, Tatsuro; Ishii, Chisato; Murata, Shota; Watanabe, Masaharu; Nomura, Fumio; et al.
Abstract : Objectives . The aim of this study was to investigate and compare the eradication rate of Helicobacter pylori as the third-line triple therapy with rabeprazole (RPZ) + amoxicillin (AMPC) + levofloxacin (LVFX) and high-dose RPZ + AMPC. Methods . 51 patients who failed Japanese first-line (proton pump inhibitor (PPI) + AMPC + clarithromycin) and second-line (PPI + AMPC + metronidazole) eradication therapy were randomly assigned at a 1 : 1 ratio to one of the following third-line eradication groups: (1) RAL group: RPZ 10 mg (b.i.d.), AMPC 750 mg (b.i.d.), and LVFX 500 mg (o.d.) for 10 days; (2) RA group: RPZ 10 mg (q.i.d.) and AMPC 500 mg (q.i.d.) for 14 days. Patients who failed to respond to third-line eradication therapy received salvage therapy. Results . The rates of eradication success, based on intention to treat (ITT) analysis, were 45.8% in the RAL group and 40.7% in the RA group. The overall eradication rates were 73.9% in the RAL group and 64.0% in the RA group. There was no significant difference between the two groups. Conclusions . The third-line triple therapy with RPZ, AMPC, and LVFX was as effective as that with high-dose RPZ and AMPC.